From Closet Talk to PC Terminology : Gay Speech and the Politics of Visibility - Pascale Smorag (Transatlantica)
This paper examines the extraordinary complexity of sexual orientations and subcultures as expressed by “gay speech,” an idiom the lesbian, gay, bisexual, and transgender community has developed for itself. Since the times when homosexuality was a perversion to today’s vibrant Prides, gayspeak has been used to express the needs of a group which, feeling socially repressed, reinvented and subverted language. Whereas some activists are using it as a means to keep politics in the language, notably by reclaiming all discriminatory terminology, others rely upon this rich lexicon to assert the diversity of their specific lifestyles and subcultures.